Comparative Analysis of Diffusers for Micro Wind Turbine - Chhetri, Roshan Kumar; Upadhyay, Dilip Bhattarai; Ghimire, Nirajan (Nepal Journal of Science and Technology, 2021)
With the increase in demand for clean energy, a micro wind turbine would be the best option for remote and urban residential areas. Installing wind turbines is not feasible in most land areas due to low or inadequate wind speed. The energy generated by the wind turbine is directly proportional to the cube of wind velocity. So, if we manage to increase wind speed slightly, it would increase energy significantly. One approach to solving problems in areas with low wind speed is using Diffuser Augmented Wind Turbine (DAWT). In DAWT, the turbine blades are typically surrounded by a duct which increases the cross-sectional area in the stream-wise direction. Since a diffuser encloses the wind turbine, the pressure behind the turbine will drop, which results in an increasing wind velocity. Different types of diffusers have been introduced to increase wind velocity. The main aim of the research is to perform a comparative analysis of four different types of diffusers to increase the power output of wind turbines. The CFD simulation of Plain Diffuser, Plain Diffuser with Inlet Shroud, Flanged Diffuser, and Flanged Diffuser with Inlet Shroud is performed to determine the maximum velocity each diffuser produced. With the solution from the simulation, a comparative analysis of each diffuser is conducted, and the results are further verified with the previous studies on DWAT. And Flanged Diffuser is found to be optimum with an increase in power generation up to 3.6 times compared to a bare wind turbine.